DELAY ANALYSIS USING IN-DEPTH INTERVIEW METHOD: CASE STUDY POST-DISASTER RECONSTRUCTION IN LOMBOK - Amar, Tsulis Iq'bal Khairul; Saputri, Utamy S; Rozandi, Ardin (ASTONJADRO, 2022)
Earthquake disasters have a significant impact, especially on infrastructure, socio-economy, and housing. In August 2018, there were earthquakes in Lombok; the Government then issued a reconstruction policy, especially in the housing sector. In the worst affected areas in North Lombok, the reconstruction process is targeted to be completed in March 2019, but as of February 2020, at least 7,210 houses have not been constructed. Further discussion is needed to determine the delay factors in post-disaster housing reconstruction. A qualitative approach was chosen to emphasize the benefits and information gathering by exploring the phenomenon under study. Seven informants from representatives of the Government, facilitators, and the community were selected to be interviewed regarding the delays. The data analysis used in this study used a descriptive approach by categorizing the results of the interviews according to previous research and experts. Thus, data analysis was found five issues of delay that are closely related to communication and coordination, human resources, materials and supplies, workmanship and quality, and monitoring.